1985
DOI: 10.1121/1.392900
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of auditory-nerve fibers to changes in intensity: A dichotomy between decrements and increments

Abstract: Adaptation of auditory-nerve responses was investigated by applying increments and decrements in intensity to an ongoing tonal background. The change in firing rate produced by a change in intensity was obtained as a function of the time delay from the onset of the background to the onset of the change in intensity. The initial change in firing rate was measured using both small (1 ms) and large (10 ms) time intervals in order to evaluate properties of rapid and short-term adaptation, respectively. Consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…In particular, a number of neurophysiological studies of auditory nerve (AN) recordings (e.g., Smith and Zwislocki, 1971;Smith, 1979;Smith et al, 1985) strongly imply a role for peripheral adaptation. More recently, Delgutte and colleagues (Delgutte, 1980(Delgutte, , 1986(Delgutte, , 1996Delgutte et al, 1996;Delgutte and Kiang, 1984) have established the case for a much broader role of peripheral adaptation for perception of speech.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…In particular, a number of neurophysiological studies of auditory nerve (AN) recordings (e.g., Smith and Zwislocki, 1971;Smith, 1979;Smith et al, 1985) strongly imply a role for peripheral adaptation. More recently, Delgutte and colleagues (Delgutte, 1980(Delgutte, , 1986(Delgutte, , 1996Delgutte et al, 1996;Delgutte and Kiang, 1984) have established the case for a much broader role of peripheral adaptation for perception of speech.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Several studies have confirmed that the process of short-term adaptation is additive in nature ͑Smith and Zwislocki, 1975;Smith, 1977;Abbas, 1979͒, meaning that the change in firing rate in response to an increment/decrement in stimulus level does not greatly depend on the time between the onset and the subsequent change in level. Smith et al ͑1985͒ showed that this property also holds if increment responses are analyzed with different window lengths that separate the portions of the response associated with rapid and short-term adaptation. In contrast, the small-window decrement response decreases with increasing time delay ͑i.e., decrement responses are not additive over a short time window following the decrement͒.…”
Section: Introductionmentioning
confidence: 99%
“…First, the effective auditory level of the components of the precursor declines over its duration because of adaptation. Second, while adaptation reduces the auditory response to existing components, it does not change the size of the increase in the auditory response produced by energy added to existing components (e.g., see Smith, 1979;Smith, Brachman, & Frisina, 1985). Hence, the components whose levels are raised to define the test stimulus produce a greater auditory response than the unchanging components.…”
Section: Possmle Bases Of the Dsv Effectmentioning
confidence: 99%